Prehydration with glycerol does not improve cycling performance vs. 6% CHO-electrolyte drink - Lamb, D. R.; Lightfoot, W. S.; Myhal, M. (Medicine & Science in Sports & Exercise, 1997)
"Ingestion of carbohydrate (CHO) solutions before and during endurance exercise often improves performance vs. placebo; prehydration with glycerol solutions may have a similar effect, presumably by expanding plasma volume." (p. S249) Ss (N = 13) were male trained cyclists. It was found that glycerol prehydration offered no apparent physiological or performance advantage over prehydration with 6% CHO. Implication. Use of glycerol as a pre-performance hydration substance provides no benefits that cannot be achieved with a common CHO drink.